Ghrelin Is a Regulator of Glucagon-Like Peptide 1 Secretion and Transcription in Mice - Lindqvist, Andreas; Shcherbina, Liliya; Fischer, Ann-Helen Thorén; Wierup, Nils (Frontiers in Endocrinology, 2017)
The gut hormones ghrelin, glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP) have been intensively studied for their role in metabolism. It is however not well known whether the hormones interplay and regulate the secretion of each other. In the present study, we investigated the effect of ghrelin on GLP-1 secretion during an oral glucose tolerance test (OGTT) in mice. Intravenous administration of ghrelin caused increased GLP-1 secretion during the OGTT. On the other hand, ghrelin was without effect on circulating levels of glucose, insulin and GIP. Furthermore, ghrelin treatment reduced proglucagon mRNA expression in GLUTag cells. In support of a direct effect of ghrelin on GLP-1 secretion, expression of the ghrelin receptor (GHS-R1a) was evident in human and murine ileal L-cells, as well as in GLUTag cells. In summary, ghrelin is a regulator of GLP-1 secretion and transcription and interfering with GHS-R1a signaling may be a way forward to enhance endogenous GLP-1 secretion in subjects with type 2 diabetes.